Occurrence of a skarn-type mineralogy found in Ciénaga Marbles, located in the NW foothills of the Santa Marta Massif (Colombia) (2016)
The early Cretaceous Ciénaga Marbles that crop out in the NW foothills of the Santa Marta Massif (Colombian Caribbean region) present an epigenetic mineral assemblage (skarn-type), overprinting the metamorphic mineral assemblage previously developed along the regional metamorphic history that affected this unit. The skarn-type mineralogy allows at least three paragenetic contexts to be distinguished, which are represented by the following neoformed minerals: (a) garnet, forsterite, diopside, titanite, wollastonite and calcite (early anhydrous metamorphic stage), (b) actinolite, tremolite, allanite and clinohumite (metasomatic or hydrated stage), and (c) chlorite, serpentine, sepiolite and quartz (late low temperature retrograde stage, probably due to infiltration of descending meteoric waters). The skarn-type mineralogy is observed as alteration halos developed around porphyritic granodiorites emplaced as sills between anisotropy planes related to metamorphic regional foliation of rock that are considered to be the causative bodies of the skarntype mineralogy. Zircon U-Pb ages obtained from granodioritic bodies yielded an age of 55.5±0.7 Ma (Ypresian, Early Eocene). The formation of the skarn-type mineralogy in the Ciénaga Marbles is temporarily related to the formation and emplacement of hydrated silicate masses that were generated at the beginning of the subduction polarity change (i.e. when the Caribbean oceanic plate began to subduct beneath South American continental plate).